2008
DOI: 10.1038/sj.bjc.6604461
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A1*28 genotype and irinotecan dosage in patients with metastatic colorectal cancer: a Dutch Colorectal Cancer Group study

Abstract: The aim of the study was to investigate the associations between UGT1A1*28 genotype and (1) response rates, (2) febrile neutropenia and (3) dose intensity in patients with metastatic colorectal cancer treated with irinotecan. UGT1A1*28 genotype was determined in 218 patients receiving irinotecan (either first-line therapy with capecitabine or second-line as monotherapy) for metastatic colorectal cancer. TA 7 homozygotes receiving irinotecan combination therapy had a higher incidence of febrile neutropenia (18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 27 publications
1
41
0
2
Order By: Relevance
“…Differences in systemic exposure to irinotecan and SN-38 are to some extent explained by genetic variations in UGT1A1 (Paoluzzi et al, 2004) but not CYP3A . Several membrane efflux pumps have a function in the bio-distribution of irinotecan and its metabolites, of which ABCB1 and ABCC2 are of particular interest Kweekel et al, 2008). Much effort has also been made to explore associations between polymorphisms in UGTs and either toxicity or antitumour response of irinotecan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in systemic exposure to irinotecan and SN-38 are to some extent explained by genetic variations in UGT1A1 (Paoluzzi et al, 2004) but not CYP3A . Several membrane efflux pumps have a function in the bio-distribution of irinotecan and its metabolites, of which ABCB1 and ABCC2 are of particular interest Kweekel et al, 2008). Much effort has also been made to explore associations between polymorphisms in UGTs and either toxicity or antitumour response of irinotecan.…”
mentioning
confidence: 99%
“…Much effort has also been made to explore associations between polymorphisms in UGTs and either toxicity or antitumour response of irinotecan. Although there is evidence that a decreased glucuronidation (UGT1A1*28 polymorphism) causes an increased risk of neutropenia and neutropenic fever (Mathijssen et al, 2003;Kweekel et al, 2008), data regarding the antitumour effects of irinotecan-based chemotherapy are contradicting. This may be because of the fact that systemic irinotecan levels are different from intratumoural concentrations, and also because of differences in the capacity of a tumour to metabolise or excrete the drug.…”
mentioning
confidence: 99%
“…For instance, studies have revealed that patients with mutated K-RAS oncogene do not benefit from cetuximab treatment (Karapetis et al, 2008). Febrile neutropenia, one of the side effects of irinotecan, can be predicted by the uridine diphosphate glucuronosyl transferase (UGT)1A1 *28 genotype (Kweekel et al, 2008). The results of the current study, although explorative in nature, need to be confirmed in a larger, independent cohort and may serve as a basis for new candidate SNP studies of genes located in the various DNA repair pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 6-12% of the general population carries the UGT1A1*28 variant. [94][95][96][97] The incidence of this polymorphism is much lower in patients of Asian origin. 97,98 Treatment of UGT1A1*28 patients with irinotecan results in reduced metabolism and increased accumulation of the active SN-38 compound and subsequently to higher risk of myelosuppression and diarrhea, as shown in a few prospective studies.…”
Section: Genetic Alterations In Crcmentioning
confidence: 99%
“…Despite the increased risk of toxicity, patients with lower UGT1A1 enzyme activity showed similar response rates and survival than did patients with normal enzymatic activity. 95 Carboxylesterase enzymes facilitate irinotecan metabolism to the active SN-38 compound. Although various SNPs of carboxylesterase regulatory genes have been reported, there is no solid evidence and consensus regarding their significance up to now.…”
Section: Genetic Alterations In Crcmentioning
confidence: 99%